2016
DOI: 10.1073/pnas.1519508113
|View full text |Cite
|
Sign up to set email alerts
|

Ancient and modern DNA reveal dynamics of domestication and cross-continental dispersal of the dromedary

Abstract: Dromedaries have been fundamental to the development of human societies in arid landscapes and for long-distance trade across hostile hot terrains for 3,000 y. Today they continue to be an important livestock resource in marginal agro-ecological zones. However, the history of dromedary domestication and the influence of ancient trading networks on their genetic structure have remained elusive. We combined ancient DNA sequences of wild and early-domesticated dromedary samples from arid regions with nuclear micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
135
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(155 citation statements)
references
References 53 publications
10
135
0
2
Order By: Relevance
“…With the latter not being the focus of our paper, however, we did not address this aspect in full detail but concluded that transcontinental and crosscontinental transportation of bulk goods using dromedaries would offer the most plausible explanation for the lack of patterning in our data (2). As far as we understand, the authors do not challenge our conclusions but support our argument that camel caravans played a role in dispersal and genetic admixture.…”
mentioning
(Expert classified)
See 1 more Smart Citation
“…With the latter not being the focus of our paper, however, we did not address this aspect in full detail but concluded that transcontinental and crosscontinental transportation of bulk goods using dromedaries would offer the most plausible explanation for the lack of patterning in our data (2). As far as we understand, the authors do not challenge our conclusions but support our argument that camel caravans played a role in dispersal and genetic admixture.…”
mentioning
(Expert classified)
“…In the maternal (mitochondrial) haplotypes, for one, we see a panmixia in modern dromedaries, which certainly predates crossbreeding at central oases along the routes. At the time that large-scale human-mediated dispersal of dromedaries started, most of today's observed mitochondrial genome diversity was already present, secured and augmented from the ancestral diversity of the wild (now extinct) dromedaries (2).…”
mentioning
confidence: 99%
“…There are lots of additional interesting observations in the work of Almathen et al (3). For instance, their microsatellite data suggested the existence of demographic collapses before domestication, some ∼5,000-8,000 ya.…”
mentioning
confidence: 94%
“…In PNAS, Almathen et al (3) now rectify this anomaly by performing what is, to my knowledge, the first large-scale genetic analysis of the domestic dromedary.…”
mentioning
confidence: 99%
“…The main route was the central Arabian Desert route (Incense Route -South-North of Arab world) of goods traveled from Southern Arabia (currently Somalia or Yemen) through the Arabian Peninsula (currently Saudi Arabia) and Damascus region (currently Jordan and Syria) to the Phoenicians on the Mediterranean Sea (Liu, 2010). On the other hand, there was a Pilgrimage Route that Muslims traveled across the globe (North-South) to reach Islam's two holiest cities -Mecca and Medina -in the Hejaz region of Saudi Arabia (Almathen et al, 2016). Thus, Saudi Arabia exposed to animal exchange network in the past while people traveled by and/or with the animals for trading or worship purposes.…”
Section: Introductionmentioning
confidence: 99%